Status and Role of Medicinal and Aromatic Plants (MAPs) in Nepalese Livelihood - Chhetri, Vivek Thapa; Shrestha, Susmita; Thapa, Sapana; Timilsina, Sachin (International Journal of Environment, 2021)
Medicinal and aromatic plants (MAPs), a principal sub-component of Non-Timber Forest Products (NTFPs), are undoubtedly an important source of revenue and rural employment. This review paper explores the current ecological and prioritized status of MAPs by the Government and the practical significance of MAPs in bodily health, lucrative employment to the Nepalese population, and revenue opportunities to the government based on 72 published articles from 1995 to 2021. The Department of Plant Resources (DPR) reported that the number of medicinal plant species has increased from 701 in 2007 to 819 in 2016 with 285 endemic plant species from 43 families, and 238 chemically tested MAPs species for medicinal significance. MAPs are highly prevalent within the 1000-2500m elevation gradient in Nepal. GoN has categorized 30 species for economic development, 12 species for cultivation and research, 12 species for protection, and 237 species for collecting royalties. Around 100 Nepalese NTFPs/MAPs are traded, but only 20 species accounts for 80% of the total trade in terms of volume and value. Nepal ranks 42nd with a value of $7.4 million and 62nd with a value of $3.3 million in exports of MAPs and essential oils, respectively, in 2017. About 80% of the Nepalese population relies on traditional medicine for basic health needs. The NTFPs/MAPs Business Promotion Strategy specifies 20 species for product promotion across Nepal. As current data are still lacking on different uses of MAPs in Nepalese society, this comprehensive review will facilitate herbal specialists, policymakers, scientific researchers, botanists, and various key stakeholders to assure better research and increase the export of MAPs in Nepal. Therefore, this study recommends public, private, and government- agencies to contribute to the infrastructure development through competitive "field-to-market" incentives and funding for the increment of the export of MAPs that directly improve the socio-economic status of the Nepalese people.